Lumbar Sympathetic Pulsed Radiofrequency Treatment for Primary Erythromelalgia: A Case Report. Issue 1 (4th October 2016) - Lee, Jin Young; Sim, Woo Seog; Kang, Ryung A.; Lee, Eun Kyung; Yang, Jae Young; Kim, Dae Yoon
Abstract: Erythromelalgia is often refractory and resistant to many forms of treatment. Numerous therapeutic options have been tried, but effective treatment remains elusive. The sympathetic nervous system has been involved in various painful conditions of neuropathic, vascular, and visceral origin. Sympathetic block is helpful in making a diagnosis and managing pain. We report a case of excellent pain relief after lumbar sympathetic pulsed radiofrequency treatment in a patient with primary erythromelalgia of the lower extremities. This case suggests the viability of pulsed radiofrequency treatment in patients with erythromelalgia.